Effect of plant growth regulators in micropropagation of (Mentha piperita L.) plant In vitro - Heba Jabbar Kadum; Sarab Abdul Hadi Mohammed (Journal of Kerbala for Agricultural Sciences, 2025)
This study was conducted on one of the most important medicinal plants with significant pharmaceutical value, namely Mentha piperita. The aim was to propagate peppermint using tissue culture techniques and combinations of plant growth regulators to obtain pathogen-free plants in large numbers. The study was carried out in the Tissue Culture Laboratory, College of Agriculture, University of Karbala, during the fall season of 2024, and included several experiments. The first experiment investigated the effect of NaOCl at different concentrations and exposure times on sterilizing seeds used as explants. The second experiment evaluated different concentrations of growth regulators at the initiation stage. The third experiment examined two types of cytokinins at different concentrations during the multiplication stage. The sterilization experiment showed that treatment with 2% NaOCl for 15 minutes achieved the lowest contamination rate (0%) without affecting explant viability. In the second experiment, BA at 1 mg L⁻¹ resulted in the highest response rate (82.50%), while NAA at 0.1 mg L⁻¹ gave the best response among auxin treatments (66.66%). In the third experiment, BA at 2 mg L⁻¹ was superior in producing the highest shoot number, length, and fresh and dry weights of the vegetative growth, which were 34.02 branches plant⁻¹, 9.06 cm, 13.65 mg, and 3.85 mg, respectively. Regarding the effect of Kin, the concentration of 1 mg L⁻¹ gave the highest values for the number and length of shoots and their fresh and dry weights, which were 25.70 branches plant⁻¹, 7.72 cm, 13.19 mg, and 3.15 mg, respectively.